Res Ipsa - Jeffrey A. Tolbert; Remo Gramigna (Semiotic Review)
This article attempts to reconcile the semiotic model of ostension with the markedly different folkloristic use of the term. In semiotics, as well as linguistics and philosophy, ostension may be glossed as showing, rather than telling. Yet in the field of folkloristics, most invocations of ostension have regarded it as a kind of interaction with traditional narratives. Despite the significant differences between these types of ostension, we suggest that both have at their heart a concern with res ipsa, the thing itself. We first discuss the historical breadth of the concept of ostension, before presenting a simple set of ostensive types, and one “ostensive context,” building on existing scholarship on ostension. The categorical reorientation we propose here is important for several reasons. The concept of ostension in all its inflected forms pushes scholars to consider communication beyond the limits of language and into an ontological consideration of how communication and meaning can operate in the network of “things” and “objects” (rather than signs). For this reason, it also stretches the limits of semiotics, which generally deals with signs and semiosis (the action of signs). Reimagining the relationship of semiotic and folkloric ostension along these lines refocuses our attention on the communicative process that is at the heart of the earliest formulations of ostension itself. More broadly, ostension impacts cultural norms surrounding appropriate modes of communication (e.g., speaking aloud versus silently gesturing); verbal storytelling and its relationship to embodied experience; and perhaps most significantly in the 21st century, belief formation and the notion of evidentiary weight.